Acoustic field characterization of a clinical magnetic resonance‐guided high‐intensity focused ultrasound system inside the magnet bore. Issue 9 (25th July 2017) - Kothapalli, Satya V.V.N.; Altman, Michael B.; Partanen, Ari; Wan, Leighton; Gach, H. Michael; Straube, William; Hallahan, Dennis E.; Chen, Hong
Abstract : Purpose: With the expanding clinical application of magnetic resonance‐guided high‐intensity focused ultrasound (MR‐HIFU), acoustic field characterization of MR‐HIFU systems is needed for facilitating regulatory approval and ensuring consistent and safe power output of HIFU transducers. However, the established acoustic field measurement techniques typically use equipment that cannot be used in a magnetic resonance imaging (MRI) suite, thus posing a challenge to the development and execution of HIFU acoustic field characterization techniques. In this study, we developed and characterized a technique for HIFU acoustic field calibration within the MRI magnet bore, and validated the technique with standard hydrophone measurements outside of the MRI suite. Methods: A clinical Philips MR‐HIFU system (Sonalleve V2, Philips, Vantaa, Finland) was used to assess the proposed technique. A fiber‐optic hydrophone with a long fiber was inserted through a 24‐gauge angiocatheter and fixed inside a water tank that was placed on the HIFU patient table above the acoustic window. The long fiber allowed the hydrophone control unit to be placed outside of the magnet room. The location of the fiber tip was traced on MR images, and the HIFU focal point was positioned at the fiber tip using the MR‐HIFU therapy planning software. To perform acoustic field mapping inside the magnet, the HIFU focus was positioned relative to the fiber tip using an MRI‐compatible 5‐axis robotic transducer positioning system embedded in the HIFU patient table. To perform validation measurements of the acoustic fields, the HIFU table was moved out of the MRI suite, and a standard laboratory hydrophone measurement setup was used to perform acoustic field measurements outside the magnetic field. Results: The pressure field scans along and across the acoustic beam path obtained inside the MRI bore were in good agreement with those obtained outside of the MRI suite. At the HIFU focus with varying nominal acoustic powers of 10–500 W, the peak positive pressure and peak negative pressure measured inside the magnet bore were 3.87–68.67 MPa and 3.56–12.06 MPa, respectively, while outside the MRI suite the corresponding pressures were 3.27–67.32 MPa and 3.06–12.39 MPa, respectively. There was no statistically significant difference ( P  > 0.05) between measurements inside the magnet bore and outside the MRI suite for the p + and p − at any acoustic power level. The spatial‐peak pulse‐average intensities ( I SPPA ) for these powers were 312–17816 W/cm 2 and 220–15698 W/cm 2 for measurements inside and outside the magnet room, respectively. In addition, when the scanning step size of the HIFU focus was increased from 100 μm to 500 μm, the execution time for scanning a 4 × 4 mm 2 area decreased from 210 min to 10 min, the peak positive pressure decreased by 14%, the peak negative pressure decreased by 5%, and the lateral full width at half maximum dimension of pressure profiles increased from 1.15 mm to 1.55 mm. Conclusions: The proposed hydrophone measurement technique offers a convenient and reliable method for characterizing the acoustic fields of clinical MR‐HIFU systems inside the magnet bore. The technique was validated for use by measurements outside the MRI suite using a standard hydrophone calibration technique. This technique can be a useful tool in MR‐HIFU quality assurance and acoustic field assessment.